TURKIC THINKERS ON THE THEORY OF INTERNATIONAL RELATIONS: A COMPARATIVE DISCUSSION OF ALISHER NAVOI'S POLITICAL AND PHILOSOPHICAL VIEWS - Kukiboyev , Shohjahon (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
Scholars from the West, in the vein of Immanuel Kant, have offered various perspectives on the ways to achieve "Perpetual Peace." When studying political philosophy and international relations theory, their ideas are most frequently referenced. This article, however, seeks to present the issue from an Eastern perspective by demonstrating that profound discussions on this subject also exist within the East, specifically in the works of the Turkic thinker Alisher Navoi.